Respekt, autonomie a intimita pacienta jako základní komponenty uchování lidské důstojnosti - Petrovicová, Eva; Trešlová, Marie (Ošetrovateľstvo, 2016)
Aim: We investigated to what extend nurses find the possibility of retraining patient autonomy, intimacy and support of human dignity in hospital setting. We also investigated whether todays nursing (provided nursing care) fulfills patient right for human dignity from patient point of view. Method: The survey used qualitative research by the use of half structured interviews with nurses and patients from surgical and long term patient wards (LTPW). The interviews were hold in January 2015 in South Bohemian hospital in Ceske Budejovice. The research population comprised of 10 general nurses out of which were 5 from surgical ward and 5 from (LTPW). Out of 20 respondents patients were 10 from surgical ward and 10 from (LTPW). Respondent selection was random and participation was voluntary. Six questions for nurses were focused on their opinion about patient autonomy assurance, dignity care, and obstacles which hinder that. Seven questions for patients inquired their opinion about possibilities for decision making about care, and experiences how is expressed dignity and assured intimacy to them. Data were recorded, rewrote with method “pencil paper”, and concepts were made according Grounded theory analyses. Results: Expressions of nurses from surgical ward show assurance of higher measurement of patient autonomy, intimacy and human dignity support in contradiction of nurses from LTPW. This status in influenced by the number of personnel, status of patients in general and space possibilities. Most of patients are at least aware of the decision making possibility even in the circumstances when all the initiative is left to the doctor especially on LTPW. Intimacy assurance patients perceive positively. Conclusion: Today’s nursing fulfills the patient right for human dignity expressed with autonomy and intimacy probably on average level. We see the possibility for quality improvement of provided nursing care to patients not only with high tech equipment and modern aids. It is necessary to be aware all the time that especially the man with all its human needs is the center of our concern. The assurance of autonomy, intimacy and human dignity support is not possible to do with the perfect devices without human approach and understanding of the man on the base of professional communication. The communication is needed not only to know and be skilled to apply it but also to have conditions for its realization.
Keywords: Personal Autonomy; hospitalizovaní pacienti; Nursing Research; kvalitativní výzkum; Nurse-Patient Relations; Humans; lidé; Ethics, Nursing; Interviews as Topic; vztahy mezi ošetřovatelkou a pacientem; Qualitative Research; zdravotní sestry v klinické praxi; Privacy; Inpatients; osobní autonomie; důstojnost lidského života; rozhovory jako téma; ošetřovatelská etika; Nurse Clinicians; Nursing Care; ošetřovatelský výzkum; soukromí; ošetřovatelská péče; intimita pacientů; Personhood